Gaining insights into genomic regions associated with Chilo partellus resistance in teosinte-derived maize population - Kaur, Ramandeep; Kaur, Gurpreet; Navpreet,; Ashmita,; Jindal, Jawala; Kumar, Ramesh; Kumar, Pardeep; Vikal, Yogesh; Sharma, Priti (Frontiers in Genetics, 2025)
Introduction:Maize stem borer (Chilo partellus) is an important primary pest of the maize crop that feeds on leaves, cobs, and pith, leading to complete damage of the plant and hence lower productivity of maize. Teosinte is a wild progenitor of maize and an important source of genetic variability that possesses diverse alleles for resistance against biotic and abiotic stresses. Therefore, teosinte is a promising candidate for introducing genetic diversity into cultivated maize germplasm by domesticating its wild alleles.Methods:In this study, we investigated the genomic regions in F6 Teosinte derived maize mapping population (recombinant inbred lines) by crossing LM13 with Teosinte (Zea mays sps. parviglumis) during 2020 -2023. The F6 mapping population (89 lines) thus developed was subjected to genotyping by sequencing (GBS), and the polymorphic simple sequence repeat (SSR) markers were found. This population was screened against C. partellus {leaf injury rating (LIR) and % dead heart} during the Kharif seasons of 2023 and 2024 (June to September).Results:The C. partellus infestations showed significant differences among the F6 lines with respect to the measured LIR and % dead heart, where the LIR ranged from 1.7 to 7.7 in the population. The phenotypic and molecular data from the SSR and single-nucleotide polymorphism (SNP) markers were used to map the quantitative trait loci (QTLs). A total of four putative QTLs (qLIR_4.1, qLIR_9.1, qDH_1.1, and qDH_2.1) were identified on chromosomes 4, 9, 1, and 2 respectively for both the traits.Conclusion:These QTLs can be used in marker-assisted breeding to develop hybrids resistant to C. partellus. Based on a literature review, we believe that our study offers a pioneering report on identifying the QTLs associated with C. partellus resistance in maize varieties in Asia. The findings of this study are expected to be of use in the future for fine mapping, expression analyses, and marker tag development for marker-assisted selection aimed at improving maize resistance to pests.